2008
DOI: 10.1007/s00428-008-0639-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features with outcomes of a series of conventional and proximal-type epithelioid sarcomas, diagnosed over a period of 10 years at a tertiary cancer hospital in India

Abstract: Epithelioid sarcoma (ES) is an uncommon sarcoma. Lately, its variants, including proximal-type ES, have been recognized. The present study highlights clinicopathological features of 26 (65%) conventional and 14 (35%) cases of proximal-type ES. Thirty-eight percent of cases were seen in 21-30-year age group, including 77.5% cases in men. Extremities were the commonest sites in both the subtypes. Histologically, conventional-type ES displayed nodular tumor aggregates with necrosis, while proximal-type showed sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
50
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 25 publications
(63 reference statements)
1
50
1
Order By: Relevance
“…The prognostic factors for this undifferentiated tumor are not yet clearly defined, as there have been very few small studies on this entity to date [14,20]. In the study by Hasegawa et al [14], tumor size was found to be an adverse prognostic factor; survival of patients whose neoplasms measured 7.8 cm or more being significantly shorter than those with smaller tumors.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…The prognostic factors for this undifferentiated tumor are not yet clearly defined, as there have been very few small studies on this entity to date [14,20]. In the study by Hasegawa et al [14], tumor size was found to be an adverse prognostic factor; survival of patients whose neoplasms measured 7.8 cm or more being significantly shorter than those with smaller tumors.…”
Section: Discussionmentioning
confidence: 93%
“…Only 30% of the patients were alive at the last follow-up (2 months-9 years). In a recent comparative study between conventional ES (26 cases) and proximal-type ES (14 cases), Rekhi et al [20] found that the 7-year disease-free survival was 19.4% in the conventional ES and nil in the proximal subtype. The overall survival rate was also lower in the proximal ES (31.3%) than the conventional type (90.2%).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations